Diversity Trees Riverside Rindu Hati as Science Teaching Materials Oriented Disaster Mitigation - Pegi Gustari; Bhakti Karyadi; Sutarno Sutarno; Deni Parlindungan; Rendi Zulni Ekaputri; Ariefa Primair Yani; Mellyta Uliyandari (Universitas PGRI Semarang, 2023)
The diversity of plants that exist on the banks of the Rindu Hati River is overgrown with plants, one of which is a tree-loving plant that has an important role in the river ecosystem and has the potential to mitigate disasters. This study aims to identify Disaster Mitigation Oriented Tree-Habitus Plants on the Rindu Hati Riverbanks which can be used as teaching materials in the form of Learning Unit Books (BUP) to increase understanding of natural science concepts and disaster awareness. Determining the research location using purposive sampling technique and inventory of tree plants using the quadratic method with an area measuring 20 mx 20 m at the tree level, 10 mx 10 m at the pole level, and 5 mx 5 m at the sapling level. Found 18 plant species from 13 families with a total of 137 individuals. These plants have disaster mitigation potential with a diversity index at the tree level reaching 2.674 in the medium category, the pole level reaching 2.432 in the medium category and the sapling level reaching 1.791 in the medium category. Based on these findings, a BUP can be made which can facilitate students in learning about information on tree-loving plants as disaster mitigation.